Implementation of PSAK 71 and PSAK 74 in Minializing Failure of the Insurance Industry - Monica Priski Cahya Maulidya; Elvia Rosantina Shauki (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the causes of default and PSAK 71 and PSAK 74 implementation effect on the risk of default. The analysis is carried out by using Public Interest Regulation Theory. This is qualitative research with case study method. Research data are sourced from questionnaires and interviews. Data were analysed using content, thematic, and constant comparative analysis. The results indicates that defaults can occur due to: (1) fraud, (2) underreserved, (3) weak governance, (4) poor investment management and (5) insurance product portfolio, and (6) weak regulations and supervision carried out by regulators. PSAK 71 and PSAK 74 will affect insurance companies in terms of financial reporting. and more conservatives reserving process. That way, it will indirectly affect the risk management and governance of insurance companies. PSAK 71 and PSAK 74 are in accordance with Public Interest Regulation Theory because they can indirectly reduce the risk of default.